2018
DOI: 10.1111/iej.12920
|View full text |Cite
|
Sign up to set email alerts
|

Detection and function of lipopolysaccharide and its purified lipid A after treatment with auxiliary chemical substances and calcium hydroxide dressings used in root canal treatment

Abstract: 5.25% NaOCl and Ca(OH) dressings from 24 h onwards were able to induce both, loss of lipid A peaks and no detection of LPS bands, rendering a diminished immunostimulatory activity through TLR4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
0
11
0
4
Order By: Relevance
“…Nevertheless, a recent in vitro study showed that amongst 1%, 2.5% and 5.25% NaOCl, only the last one was able to induce loss of lipid A peaks and LPS bands detection (Marinho et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, a recent in vitro study showed that amongst 1%, 2.5% and 5.25% NaOCl, only the last one was able to induce loss of lipid A peaks and LPS bands detection (Marinho et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Lipid A is the bioactive component of LPS responsible for most of the host's immune response. 51,52,53,54 LTAs are present on the surface of gram-positive cells, such as Enterococcus faecalis, and have adhesive properties, as they adsorb to hydroxyapatite, binding through its lipid portion. They stimulate leukocytes, monocytes, and macrophages to release inflammatory mediators.…”
Section: Bacterial Virulence Factorsmentioning
confidence: 99%
“…In endodontic therapy, hydroxyl ions present in the calcium hydroxide paste can hydrolyze LPS, degrading lipid A and neutralizing its residual effect after cell lysis. 54,114 LPS is known to be the most toxic constituent of bacterial endotoxin, having no structural homologue among multicellular organisms. 115 In general, bacterial LPS are composed of three structural domains: lipid A, core, and repeating O-antigen.…”
Section: The Key Role Of Endotoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Other studies confirm the ability of calcium hydroxidebased medication to eliminate endotoxins at different time periods of action. 40…”
Section: Discussionmentioning
confidence: 99%